DBT Gene Mutation Among Maple Syrup Urine Disease (MSUD) In Malaysian Population - Julia Omar; Noor Azlin Azraini Che Soh; Wan Norlina Wan Azman; Aniza Mohammed Jelani; Noorazliyana Shafii; Rowani Mohd Rowi; Lock-Hock Ngu (USIM Press, 2024)
Vol. 7 No. 3 (2021): Special Issue on Clinical Scenarios In Medicine, A Malaysian Experience (Case Report)